Representasi Kekuasaan Simbolik dalam Pembelajaran Berbasis Kurikulum Merdeka Kelas X (Kajian Wacana Kritis Pierre Bourdieu) - Uswatun Hasanah; Jufri Jufri; Muhammad Saleh (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research aims to describe the representation of symbolic power in the implementation of Merdeka Curriculum-based learning in class X SMAN 9 Gowa, based on Pierre Bourdieu's critical discourse study. Pierre Bourdieu's critical discourse study. The main focus of this research is describing the forms of symbolic power through the elements of euphemization and censorship in communication between teachers and students. Data collection techniques through direct observation direct observation, recording conversations, and taking notes during the learning process. The result The results show that symbolic power is reflected in two main elements main elements: euphemization with 18 forms including; 1) Request, 2) request, 3) necessity, 4) obligation, 5) Discipline, 6) Efficiency, 7) Appreciation, 8) Distrust, 9) Confidence, 10) Competence, 11) Incompetence, 12) Comfort, 13) Expectation, 14) Policy, 15) Generosity, 16) Help, 17) Caring and 18) Usability. and sensorization with 9 forms including; 1) worship, 2) marginalization, 3) threat, 4) coercion, 5) disappointment, 6) prohibition, and 7) asking for leniency, 8) Disobedience, and 9) Selfishness. In conclusion, in the context of learning, teachers still holds the dominant authority, while students tend to accept the situation as a form of discipline. as a form of discipline.